Supportiveness of university physical environment on undergraduate students' participation in leisure-time physical activity in south-west Nigeria - Alayode Ajibua; O.A. Onanuga (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2020)
Participation in Leisure-Time Physical Activity (LTPA) has declined among university undergraduate students in Nigeria. Studies have identified the physical environment of universities as a potential cause of the decline; however, this claim has not been verified. Therefore, this study evaluates the role of the physical environment in universities in inducing student participation in LTPA. This study is necessary, as previous research has shown the involvement in LTPA helps in developing the physical, physiological, social, emotional and mental capacities of students. It is also a factor in the relief of daily stress from the heavy academic workloads of the university students. A quantitative research methodology was adopted for this study. A total sample of 2,867 students was selected from 14 public universities in South West Nigeria using a multi-stage sampling technique. It was deduced from the study that the physical environment was a determining factor for LTPA participation among university undergraduate students in South West Nigeria. In addition, it was found that the availability of facility infrastructure that encourages students roaming and safety pre-cautions on campus would enhance participation in LTPA among the university students.